2013
DOI: 10.1186/2045-8118-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-shunting observations in adult sheep with kaolin-induced hydrocephalus

Abstract: BackgroundThe objective of this study was to examine host-shunt interactions in sheep with kaolin-induced hydrocephalus.MethodsForty-two sheep (29–40 kg) were utilized for this study. In 20 animals, various kaolin doses were injected into the cisterna magna including 10 and 50 mg/kg as well as 2–4 ml of a 25% kaolin suspension. Based on animal health and hydrocephalus development, 3 ml of a 25% kaolin suspension was chosen. In 16 animals, kaolin was administered and 6–8 days later, the animals received a custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
11
2
Order By: Relevance
“…The possible cause of this difference may be due to the neglect of the hydrocephalic neonates by their mothers, neurogenic muscle atrophy, lethargy and general weakness of the hydrocephalic pups. Reduction in weight has been reported to be one of the first signs of development of hydrocephalus in experimental models (Del Bigio, 2001; López et al, 2003; McMullen et al, 2012; Johnston et al, 2013; Shaolin et al, 2015; Olopade et al, 2012). The body weight is an important index in developmental biology in neonatal pups and may be a pointer to an on-going pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…The possible cause of this difference may be due to the neglect of the hydrocephalic neonates by their mothers, neurogenic muscle atrophy, lethargy and general weakness of the hydrocephalic pups. Reduction in weight has been reported to be one of the first signs of development of hydrocephalus in experimental models (Del Bigio, 2001; López et al, 2003; McMullen et al, 2012; Johnston et al, 2013; Shaolin et al, 2015; Olopade et al, 2012). The body weight is an important index in developmental biology in neonatal pups and may be a pointer to an on-going pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological analysis of Iba-1microglia cells suggested that microglial reactivity was mostly limited to the cellulose lamina tract. Additionally, hydrocephalus produced a thinning of the corpus callosum, but did not lead to an obvious loss of myelin staining as well as reactive astroglial changes in the white matter (Johnston et al, 2013). To evaluate the effects of hydrocephalus along the ventricular walls, we quantified the number of GFAP+ astrocytes lining the striatal wall of the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…16 To facilitate the use of shunt systems that are similar in size and design to their human counterparts, a large animal model must be created. 17 A hydrocephalic sheep model to evaluate ventriculo-peritoneal shunts has been described in a previous study. 17 The purpose of this pilot study is to assess the suitability and feasibility of a goat model (specifically 'Saanen breed' goats, which are very similar to sheep) for evaluating the implantation technique and design of the ventriculosinus shunt.…”
Section: Introductionmentioning
confidence: 99%
“…17 A hydrocephalic sheep model to evaluate ventriculo-peritoneal shunts has been described in a previous study. 17 The purpose of this pilot study is to assess the suitability and feasibility of a goat model (specifically 'Saanen breed' goats, which are very similar to sheep) for evaluating the implantation technique and design of the ventriculosinus shunt. Since hydrocephalus is not required for addressing the research question, a nonhydrocephalic model was chosen.…”
Section: Introductionmentioning
confidence: 99%